Modifying 5-HT1A Receptor Gene Expression as a New Target for Antidepressant Therapy - Albert, Paul R.; Le François, Brice (Frontiers in Neuroscience, 2010)
Major depression is the most common form of mental illness, and is treated with antidepressant compounds that increase serotonin (5-HT) neurotransmission. Increased 5-HT1A autoreceptor levels in the raphe nuclei act as a “brake” to inhibit the 5-HT system, leading to depression and resistance to antidepressants. Several 5-HT1A receptor agonists (buspirone, flesinoxan, ipsapirone) that preferentially desensitize 5-HT1A autoreceptors have been tested for augmentation of antidepressant drugs with mixed results. One explanation could be the presence of the C(-1019)G 5-HT1A promoter polymorphism that prevents gene repression of the 5-HT1A autoreceptor. Furthermore, down-regulation of 5-HT1A autoreceptor expression, not simply desensitization of receptor signaling, appears to be required to enhance and accelerate antidepressant action. The current review focuses on the transcriptional regulators of 5-HT1A autoreceptor expression, their roles in permitting response to 5-HT1A-targeted treatments and their potential as targets for new antidepressant compounds for treatment-resistant depression.